Perancangan Sistem Kendali pada Lengan Assistive Social Robot menggunakan Kamera - Riky Tri Yunardi; Ronny Mardiyanto (JURNAL NASIONAL TEKNIK ELEKTRO, 2017)
Robotics technology has widely applied and developed in the rehabilitation field. Assistive Social Robot is a technology that can interact with users and improve progress in rehabilitation. Accessibility when taking an object using a robotic arm system is needed. A camera is the optical sensor that has been applied to detect the position of the object. In this paper explain a design of control system of robotic arm by using a camera. Information of the distance and position are used to organizing the control of the robotic arm movement, that form of a gripper. Tests conducted include: testing to detect the contour of the object, testing the measurement of object distance, and testing the robot arm control. From the results shows the speed of performance of control system that has been designed in performing the task to pick up an object from the initial position to the end takes 28.05 seconds.Keywords : Assistive social robot, robotic arm , cameraAbstrak—Teknologi robotika telah banyak diaplikasi dan dikembangkan dalam bidang rehabilitasi. Assistive Social Robot merupakan suatu teknologi robotika yang dapat berinteraksi dengan pengguna dan memberi bantuan dalam pemulihan proses rehabilitasi. Aksesibilitas ketika mengambil sebuah benda dengan menggunakan sistem lengan robot sangat dibutuhkah. Kamera merupakan sensor optik yang paling banyak diaplikasikan untuk mendeteksi posisi objek. Artikel ini membahas mengenai sistem kendali lengan robot menggunakan kamera. Informasi jarak dan posisi objek digunakan untuk mengendalikan gerakan lengan robot robot yang berbentuk gripper. Pengujian yang dilakukan meliputi: pengujian mendeteksi kontur objek, pengujian pengukuran jarak objek, serta pengujian kendali lengan robot. Dari hasil menunjukkan kecepatan kinerja sistem kendali yang telah dirancang dalam melakukan tugas untuk mengambil sebuah objek dari posisi awal sampai akhir memerlukan waktu 28,05 detik.Kata Kunci : Assistive social robot, lengan robot, kamera